LEGAL AND ILLEGAL ACTIONS "CONFRONTATION": SOCIO-PHILOSOPHICAL DIMENSION - Kharchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
It is confirmed that leveling of natural law as a basic tradition generates a "new normality" having no border between legal and illegal actions. The aim of the study is to analyze the content of the terms "legal action" and "illegal action" with a view to their further conceptualization. The key task is to comprehend the phenomenon of "conflict" between legal and illegal actions in terms of philosophical ontology, social philosophy, and philosophy of law. Philosophical-legal, philosophical-linguistic, as well as comparative methodological principles have shown that social cognition of legal reality proceeds in the procedures of understanding, interpreting, mastering social reality, but there is no complete understanding, which gives rise to confrontation between legal action and illegal action. The conclusions prove that "legal action" forms the basic principles of legal behavior as a socially significant external practical activity. "Illegal action", in turn, is the opposite factor, upsetting the balance of social relations, leveling or destroying tradition.